ANTIMICROBIAL DRUG RESISTANCE EVALUATION AND MONITORING IN ESCHERICHIA COLI ISOLATED FROM POULTRY ENVIRONMENT AT DIFFERENT TIME INTERVALS - Anwar, Rozina; Khan, M Altaf (Biological Sciences - PJSIR, 2020)
A high prevalence of multiple drug resistance was observed in populations of E. coli isolated in 1992-93 from poultry carcasses, fluff, hatchery environment and water at different broiler farms in Karachi, Pakistan. Five hundred isolate of E. coli were made of which 375 were tested for their sensitivity to five antimicrobials using the tube dilution method. Similarly, during 1995-96, 430 E. coli isolates were made (from the same farms) of which 315 were tested for their sensitivity to the same antimicrobials studied in 1992-93. coli isolates during 1992-93 and 1995-96 showed increase in resistance from 50 to 56% against amoxycillin, from 62 to 71% against neomycin, from 97 to 100% against oxytetracy- cline, from 95 to 100% against tetracycline and from 95 to 98% against trimethoprim. It appears that exposure of E. coli of poultry origin in Pakistan to the five studied antimicrobials could well be the cause of increasing antimicrobials resistance. This data supports the growing contention that subtherapeutic doses of antimicrobials should be eliminated as a means of promoting rapid growth.